Hubungan Kemampuan Berpikir Kreatif dengan Kemampuan Menulis Cerpen (Studi Korelasional pada Siswa SMA Negeri 39 Jakarta) - Anggun Citra Dini Dwi Puspitasari (Universitas Indraprasta PGRI Jakarta, 2017)
The objective of this research is to know whether there is any correlation between creative thinking and short story writing abilities. This research is conducted at XI grade of SMA Negeri 39 in Jakarta, with the sample consisting of 40 students. The research employs a survey method by applying regression and correlation analysis techniques. Further, the result of the research indicates that there is a positive and significant correlation between creative thinking ability (X) and short story writing ability (Y), as shown by the (r) value of 0,902 and regression equation of ? = 20,261 + 0,707X.